Lessons Learned from Developing Plain Language Summaries of Research Studies - Maureen Maurer; Joanna E. Siegel; Kirsten B. Firminger; Jane Lowers; Tania Dutta; Jane S. Chang (SLACK Incorporated, 2021)
Background: Plain language translation may facilitate the public's ability to understand and use results of scientific research. Brief description of activity: This article describes the Patient-Centered Outcomes Research Institute's (PCORI) approach to and lessons learned from developing plain language summaries of PCORI-funded research for the lay public. Implementation: We developed and tested a standard template for the summaries, incorporating feedback in the template design from focus groups with members of the public. Between February 2017 and March 2020, we completed translation of 272 plain language summaries of PCORI-funded studies, covering topics including cardiovascular disease, obesity, cancer, mental health, asthma, HIV/AIDS, and comparative effectiveness research methods. Results: Templates use a question-and-answer format, with sections on the rationale, methods, results, limitations, and how the research will help inform decisions. In addition to feedback on template heading wording and order, focus group participants stressed the importance of establishing relevance and conveying credibility and limitations. Lessons learned: Lessons learned relate to supporting consistency across individual summaries, carefully prioritizing content to include in the summaries, and balancing plain language and reading level with precision. These lessons learned from template development and implementation may be useful to other organizations or publishers contemplating similar efforts to make scientific research results more accessible. [HLRP: Health Literacy Research and Practice. 2021;5(2):e155-e161.] Plain Language Summary: The Patient-Centered Outcomes Research Institute (PCORI) funds comparative effectiveness research. This research compares the benefits and harms of two or more health care choices. In this article, we describe lessons learned from PCORI's efforts to develop plain language summaries of results from the research it funds. These lessons may help other organizations that want to share research results in plain language.